Electrode/electrolyte interface and interface reactions of solid oxide cells: Recent development and advances - He, Shuai; Jiang, San Ping (Progress in natural science, 2021)
High temperature solid oxide cells (SOCs) consisted of solid oxide fuel cells (SOFCs) and solid oxide electrolysis cells (SOECs) are considered one of the most environmentally friendly and efficient energy conversion technology to store renewal energy from sun and wind in hydrogen and generate electricity from the fuels such as hydrogen and natural gas with high efficiency and very low greenhouse gas emission. Over the last few decades, the development of SOC technologies in particularly SOFCs has experienced significant progress and much of the recent research have paid great efforts in understanding the processes occurring at the electrode/electrolyte interfaces. As electrochemical reactions mainly proceed at the gas, electrode and electrolyte three phase boundaries (TPBs), the microstructure and properties of the electrode/electrolyte interfaces thus play a crucial role in determining the overall cell performance and durability. Herein, we review the progress and achievements in the fundamental researches of the electrode/electrolyte (mainly oxygen-conducting) interface evolution behavior under open circuit and polarization conditions. Studies involving interfacial phenomena such as interface formation and reactions, element segregation and diffusion, micropore formation and delamination are summarized and discussed in detail. Besides, the state of the art characterization techniques that have been employed to examine the interface behavior are reviewed. Finally, the challenges and prospects of the interface research in the improvement of the performance and durability of a SOC device are discussed.